Towards parameters and protocols to recommend FES-Cycling in cases of paraplegia: a preliminary report - Juliana Araujo Guimarães; Lucas Oliveira da Fonseca; Clarissa Cardoso dos Santos-; Antônio Padilha Lanari Bó; Charles Fattal; Christine Azevedo-Coste; Emerson Fachin-Martins (PAGEPress Publications, 2016)
Functional Electrical Stimulation assisted cycling (FES-Cycling) is increasingly becoming an alternative option recommended to people with spinal cord injury struggling with paraplegia and interested in practicing sports. In order to propose preconditions to guide FES-Cycling recommendation, we aimed to investigate some features and their potential relationships with responsiveness to Neuromuscular Electrical Stimulation (NMES). Fourteen volunteers attended a public recruitment forum to be assessed about their responsiveness through the 16-sessions of NMES. Volunteers were separated in two groups (responsive and non-responsive to NMES) which were investigated in the light of some personal, clinical, structural and functional features. Fifty seven percent of the initial sample responded to electrical stimulation with a visual contraction. This responsive group was predominantly composed by subjects presenting traumatic spinal cord injuries above T12 vertebral level. Only two subjects became responsive at the 3rd and 16th sessions. Among the observed features, the etiology and level of injuries seems to be more associated to responsiveness. Our observations seem to indicate that subjects with traumatic spinal cord injury above T12 level were the best potential candidates for FES-cycling.